Exploring the influence of financial instrument prices on Türkiye‘s credit volume during COVID -19 - Tekin , Bilgehan; Dirir, Sadik Aden (Studia Historiae Oeconomicae, 2025)
This study addresses a critical question for financial stability: can fluctuations in financial investment instruments, specifically during crises, explain variations in credit volume? This issue is particularly relevant for economies like Türkiye, where COVID-19 introduced significant financial volatility. Using weekly data from January 6, 2020, to July 4, 2022, this paper investigates the relationship between key financial assets and Türkiye's credit volume, employing a Non-linear Autoregressive Distributed Lag (NARDL) model to capture asymmetric responses to both positive and negative price shocks. To enhance robustness and precision in estimating long-term relationships, cointegration approaches such as Fully Modified Ordinary Least Squares (FMOLS) and Dynamic Ordinary Least Squares (DOLS) are utilized. The results reveal significant asymmetric effects, with negative shocks to bond rate and bitcoin exerting stronger adverse impacts in the long run, while positive Borsa Istanbul shocks enhance credit volume. Gold and USD exhibit mixed effects. Findings underline that policymakers need to monitor asset price changes carefully, as they can amplify credit market risks. Specifically, targeted measures to manage volatility in exchange rates and bond yields could help maintain balanced credit growth, reducing systemic risk in times of economic uncertainty. This research contributes to the literature by highlighting the asymmetric effects of financial instruments on credit volume during the pandemic, offering valuable insights for financial stability policy in emerging markets like Türkiye.